The Implementation of Ethical Codes in Scientific Writing: Maintaining Students’ Academic Credibility in the Digital Era - Nuphanudin; Jihan Lailatul Fadhilah; Alvina Nur Elysia (The Indonesian Institute of Science and Technology Research, 2026)
Integrity of academic work is a fundamental aspect of higher education, especially in the digital era where information is easily accessible. This study explores the implementation of the ethical code in scientific writing and its role in maintaining students’ academic credibility. Using a qualitative descriptive approach, data were collected through interviews, focus group discussions, and document analysis involving undergraduate students and lecturers. The findings reveal varying levels of understanding and application of ethical principles among students, with challenges including easy access to information, reliance on digital tools, and limited practical ethics training. The study highlights the crucial role of institutions and educators in fostering ethical awareness through continuous and contextually relevant education. This research contributes to the discourse on academic integrity by emphasizing the need for an integrative approach to ethics education that adapts to the complexities of the digital age.